The Kualitas Kacang Tanah (Arachis hypogeae L.) Kefir dengan Variasi Konsentrasi Starter Ragi dan Lama Fermentasi - Pratika Viogenta; Nani Kartinah; Amalia Khairunnisa; Fathur Rahman (Biota, 2021)
One of the fermented milk products, namely kefir, is increasingly popular because it has many health benefits. Peanut juice has a high enough protein content that it can be used as a substitute for animal milk. The purpose of this study was to determine the quality of peanut kefir with variations in the concentration of ragi tape inoculum and fermentation time. This research method used 3 variations in the concentration of tape yeast (1, 2 and 4%) and long fermentation time (24, 48 and 72 hours). The results showed that the highest total LAB was in 4% ragi tape inoculum with a fermentation time of 24 hours (4.4x108 cells/mL) and the lowest was in 4% tape yeast inoculum with a fermentation time of 72 hours (9.8x107 cells/mL) and total yeast between 1x104 cells/mL - 3x105 cells/mL) and alcohol produced <1%. Total acid obtained between 6% - 17.6%. The increase in total acid is proportional to the decrease in pH. The pH of the peanut kefir medium was between 3.44 - 4.12. Peanut kefir with tape yeast inoculum meets the standard requirements for fermented milk and can replace milk kefir.